Effect of Using Geogebra-Based Interactive Media on Junior High School Students' Understanding of Geometry Concepts - Adrian Maulana; Lalu Sucipto; Baiq Rofina Arvy (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Inovative and engaging learning media are needed to improve students’ participation and conceptual understanding, particularly using GeoGebra-based interactiv media. This research aimed to investigate the effec of GeoGebra-based interactiv media on students understanding of spatial geometry concept. The study employed aaquantitative method using a quasi-experimental approach with a pretest–posttestccontrol group design. The population consisted of allaeighth-grade student of SMPIT Jihadul Muslimin Batu Pengilik, East Lombok, in the 2025/2026 academic year. Samples were selecteduusing a cluster random sampling techniqe, with class VIII A assigned as theeexperimentaligroup and class VIII B assthe control group, each consisting of 20 students. The experimentallgroup received instruction throught GeoGebra-based interactive media, while the control group used PowerPoint media. The research instrument was a validated test of students understanding of spatial geometry concept. Data analysis was conducted using descriptive statistics, the Shapiro–Wilk normality test, Levene’s Test for homogeneity and the Independent Sample t-test with the assistance of SPSS 25. The findings revealed that the experimental group achieved an average posttest score of 83.70, while the control group obtained 75.90. Hypothesis testing produced a significanc value of 0.001 < 0.05, indicating that GeoGebra-based interactive media significantly affected students’ conceptual understanding. In addition, the pretest analysis showed no significan differenc between the two group (Sig. = 0.128 > 0.05), indicating relatively equivalent prior abilities. Effec size analysis using Cohen’s d showed aamoderate effec on the pretest (0.50) and a strong effect on the posttest (1.17). These results demonstrate that GeoGebra-based interactive media effectively improves students’ understanding of spatial geometry concepts through interactive and meaningful learning experiences.